Analysis of the oral microbiome composition of healthy individuals and the in vitro antibacterial activity of platelet-rich fibrin from these individuals against oral pathogenic bacteria - Popowski, Wojciech; Domanowska, Dominika; Koseski, Damian; Ostrowski, Rafał; Zalewska, Magdalena; Małecka-Giełdowska, Milena; Łasica, Anna; Popowska, Magdalena (Frontiers in Microbiology, 2025)
Platelet-rich fibrin (PRF) is a platelet concentrate widely applied in various medical fields and is considered a valuable adjunct in tissue regeneration during surgical procedures. However, infections caused by biofilm-forming bacteria at surgical sites, combined with increasing antibiotic resistance, present a major clinical concern. Current research is focused on identifying alternative therapeutic strategies to improve infection control and promote wound healing. This study aimed to characterize the oral microbiome of healthy individuals and evaluate the in vitro antimicrobial properties of two PRF formulations. The antibacterial activity, along with its temporal dynamics at different initial bacterial concentrations, was assessed against Gram-negative bacteria (Escherichia coli, Porphyromonas gingivalis) and Gram-positive bacteria exhibiting diverse morphologies (Bacillus subtilis, Micrococcus luteus, Staphylococcus lentus, Enterococcus casseliflavus, Streptococcus mutans). Our results fill gaps in knowledge concerning the spectrum of PRF’s antimicrobial activity, demonstrating efficacy against a range of opportunistic and pathogenic bacteria. Key findings include the absence of significant differences in oral microbiome composition between male and female participants, a lack of inhibitory effect of A-PRF against S. mutans, and a transient inhibitory effect against P. gingivalis observed only at low initial OD₆₀₀ and within 24 h. These findings indicate that A-PRF therapy alone may not provide a sufficiently effective antibacterial effect in patients with oral infections, and that alternative or adjunctive therapeutic approaches should be considered in such cases.